Pengaruh Gaya Kepemimpinan Transformasional dan Budaya Organisasi Terhadap Kinerja Karyawan CV. Mulia Abadi Kota Pasuruan - Umdatul Amiroh; N. Rachma; Alfian Budi Primanto (UNIVERSITAS ISLAM MALANG, 2021)
Abstract This aims of this research is to determine the effect of transformational leadership styles and organizational culture on employee performance CV. Mulia Abadi Pasuruan City. The type of analysis used is explanatory research and using quantitative methods. Collecting data using questionnaires from population with 45 employees, the sample used is as many as 45 respondents. The data analysis method used is multiple linear regression analysis.The result of the study showed that:(1) the transformational leadership style and organization culture has a simultaneous significant effect on the employee performance CV. Mulia Abadi Pasuruan City, (2) The transformational leadership style has a significant effect on employee performance CV. Mulia Abadi Pasuruan City, (3) The organization culture has a significant effect on empoloyee performance CV. Mulia Abadi Pasuruan City. Keywords: Transformational Leadership Style, Organization Culture and Employee Performance